Comparison Between Burden of Care Partners of Individuals with Alzheimer’s Disease Versus Individuals with Other Chronic Diseases - Murat Demirbas; Julie H. Hahn-Pedersen; Henrik L. Jørgensen (Neurology and Therapy, 2023)
Abstract Background Caregiving in Alzheimer’s disease (AD) is often provided by informal care partners, who spend more hours per week on average than care partners of individuals with conditions other than AD. However, the burden of care in partners of individuals with AD has not been systematically compared to that of other chronic diseases. Objective The current study therefore aims to compare the care partner burden of AD to that of other chronic diseases through a systematic literature review. Methods Data was collected from journal articles published in the last 10 years, using two unique search strings in PubMed and analysed using pre-defined patient-reported outcome measures (PROMs) including the EQ-5D-5L, GAD-7, GHQ-12, PHQ-9, WPAI and the ZBI. The data was grouped according to the included PROMs and the diseases studied. The number of participants in the studies reporting burden of caregiving in AD was adjusted to reflect the number of participants in studies reporting care partner burden in other chronic diseases. Results All results in this study are reported as a mean value and standard deviation (SD). The ZBI measurement was the most frequently used PROM to collect care partner burden (15 studies) and showed a moderate burden (mean 36.80, SD 18.35) on care partners of individuals with AD, higher than most of the other included diseases except for those characterized by psychiatric symptoms (mean scores 55.92 and 59.11). Other PROMs such as PHQ-9 (six studies) and GHQ-12 (four studies) showed a greater burden on care partners of individuals with other chronic diseases such as heart failure, haematopoietic cell transplantations, cancer and depression compared to AD. Likewise, GAD-7 and EQ-5D-5L measurements showed a lesser burden on care partners of individuals with AD compared to care partners of individuals with anxiety, cancer, asthma and chronic obstructive pulmonary disease. The current study suggests that care partners of individuals with AD experience a moderate burden, but with some variations depending on the PROMs used. Conclusion The results of this study were mixed with some PROMs indicating a greater burden for care partners of individuals with AD versus other chronic diseases, and other PROMs showing a greater burden for care partners of individuals with other chronic diseases. Psychiatric disorders imposed a greater burden on care partners compared to AD, while somatic diseases in the musculoskeletal system resulted in a significantly smaller burden on care partners compared to AD.